2020
DOI: 10.1037/ort0000445
|View full text |Cite
|
Sign up to set email alerts
|

Teachers victimizing students: Contributions of student-to-teacher victimization, peer victimization, school safety, and school climate in Chile.

Abstract: Although most of the school violence literature is focused on peer victimization, interest is growing in teachers being victimized by their students. However, there is far less interest in students being victimized by their teachers, patterns of mutual victimization, and how they are associated with other school factors. Using the conceptual framework of school violence in evolving contexts, the present study examined teacher-to-student victimization in Chile and tested, for the first time, the associations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 57 publications
0
19
1
Order By: Relevance
“…Previous studies demonstrate a general agreement that exposure to peer victimization and community violence results in psychological distress, such as depressive symptoms [ 75 , 76 ]. This relationship or strength may vary by the nature and context of violent experiences, such as victimization or witnessing an event, and also when (other) post-traumatic stress, individual characteristics, and socioeconomic environments are accounted for [ 77 , 78 ]. Our study tells that exposure to violence in childhood and adolescence is accompanied by a higher risk of depressive symptoms compared to the low adversity class, yet not through self-esteem; also, a lower risk than Household Dysfunction but not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrate a general agreement that exposure to peer victimization and community violence results in psychological distress, such as depressive symptoms [ 75 , 76 ]. This relationship or strength may vary by the nature and context of violent experiences, such as victimization or witnessing an event, and also when (other) post-traumatic stress, individual characteristics, and socioeconomic environments are accounted for [ 77 , 78 ]. Our study tells that exposure to violence in childhood and adolescence is accompanied by a higher risk of depressive symptoms compared to the low adversity class, yet not through self-esteem; also, a lower risk than Household Dysfunction but not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this theoretical framework, the authors have conducted a series of studies on various aspects of students' and teachers' victimization, in schools in several places around the world (López et al, 2020). The model guides the literature review and the study hypotheses.…”
Section: A Theoretical Frameworkmentioning
confidence: 99%
“…On the one hand, research has suggested that the victimization of students by teachers is related to the victimization of teachers by students. This spiral of aggression is known as cross victimization (Khoury-Kassabri, 2006;López et al, 2020). The explanatory hypothesis of this spiral of violence is related to teachers' beliefs that through their own aggression, they might stop the aggression of students or achieve the academic objectives that the school has demanded of them (Innes and Kitto, 1989;Emmer and Hickman, 1991).…”
Section: Introductionmentioning
confidence: 99%